Institutionalizing technical assistance the case of Zamboanga del Sur rural development project - Ibay, Alejandro B. (Philippine Journal of Public Administration, 1984)
The Zamboanga del Sur Development Project which commenced in 1972 with substantial grants from the Government of Australia adopted institutionalization as a strategy to sustain the development activities it started in the province. As a result, the Project acquired, in addition to its responsibility of uplifting the economic and social conditions of project beneficiaries, the functions of planning, structuring and guiding local institutions on matters of technology transfer, fostering changes in values and in orientations, and obtaining support from the government. Viewed in the context of institution building variables like leadership, doctrine, program, resources, structure and linkages, Zamboanga's experience reflects bureaucratic incursions in the implementation of Project activities. Its role of institutionalizing development techniques, values and attitudes is confronted with problems of financial shortages, fast personnel turnover, ineffectual inter-agency coordination, insufficient leadership support and weak commitment of higher authorities. Solutions to these problems determine success or failure of the project, both its component activities and its institutionalization.